Preparation method of supercapacitor material

By preparing cobalt and nickel in the cathode material of the waste lithium battery into a leachate solution, and combining hydrothermal reaction and thiourea heat treatment, supercapacitor electrode materials with excellent electrochemical properties were prepared, solving the problems of low transition metal reuse efficiency and uncontrollable material form in the prior art.

CN119852103APending Publication Date: 2025-04-18HEBEI UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311341885.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-17
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In the existing lithium-ion battery recycling technology, the reuse efficiency of transition metals is low, and the form of the obtained material is uncontrollable, which affects performance.

Method used

By preparing cobalt and nickel in the cathode material of the used lithium battery in leaching solution, combining phenylatic acid and polyvinylpyrrolidone for hydrothermal reaction, a supercapacitor electrode material precursor (NixCo3-x-MOF) was obtained, and mixed with thiourea for heat treatment, a supercapacitor electrode material (NixCo3-x-S) with good electrochemical properties was prepared.

Benefits of technology

The high porosity and large specific surface area of ​​supercapacitor electrode materials are achieved, and the electrochemical performance is excellent. Especially at a current density of 1A/g, the specific capacitance of supercapacitor electrode materials can reach up to 595C/g (~1190F/g).

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852103A_ABST
    Figure CN119852103A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a supercapacitor material, which comprises the following steps: S1, mixing a first solution, a second solution, trimesic acid, polyvinylpyrrolidone, N, N-dimethylformamide, absolute ethyl alcohol and water, stirring until the mixture is transparent, and performing hydrothermal reaction to obtain a supercapacitor material precursor, the first solution meets the first condition and / or the second solution meets the second condition, in the first condition, all or part of cobalt ions in the first solution come from the first leaching solution, and in the second condition, all or part of nickel ions in the second solution come from the second leaching solution; and S2, in an argon or inert gas atmosphere, in a tubular furnace, placing the supercapacitor material precursor in the downstream of the airflow of thiourea, heating the thiourea to sublimate the thiourea, and meanwhile, carrying out heat treatment on the supercapacitor material precursor at 300-400 DEG C for 1-3 hours to obtain the supercapacitor material. The supercapacitor electrode material precursor is synthesized through the hydrothermal method, and the technical scheme is low in cost and easy to operate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of supercapacitors, and in particular relates to a method for preparing a supercapacitor material. Background Art

[0002] As a typical energy storage battery, lithium-ion batteries have been widely used in mobile phones, laptops, electronic cars and other fields due to their advantages such as light weight, high energy density, lead-free, cadmium-free and environmentally friendly. It is predicted that by 2026, the global market value of lithium-ion batteries will reach 139 billion US dollars. With the increase in demand for lithium-ion batteries, the cycle of general lithium-ion batteries is between 500 and 800 times, and the life of power lithium-ion batteries can reach 2,000 cycles. In addition, due to the continuous development of energy storage technology, the requirements for battery performance are gradually increasing, resulting in a large number of waste lithium-ion batteries.

[0003] There are three main methods for recycling waste lithium-ion batteries: physical, chemical and biological. The physical method uses the physical and chemical reaction process to treat lithium iron phosphate batteries. Common physical and chemical treatment methods are mainly crushing flotation and mechanical grinding. The chemical method is a method of treating lithium-ion batteries using a chemical reaction process, which is generally divided into two methods: pyrometallurgy and hydrometallurgy. The biological method of biometallurgy is also currently under research, which uses the metabolic process of microorganisms to achieve selective leaching of metal elements such as cobalt and lithium. The biological method has low energy consumption, low cost, and microorganisms can be reused with little pollution; however, the cultivation of microorganisms requires harsh conditions, long cultivation time, low leaching efficiency, and the process needs to be further improved.

[0004] The recycling of transition metals in waste lithium-ion batteries is also a hot topic at present. CN110756191A discloses a method for wet recovery of waste lithium cobalt oxide batteries using citric acid and using the leached solution as a cobalt source to synthesize CoPi catalysts, but the disadvantage of leaching using organic acids is that the efficiency is low. CN111048862A discloses a method for wet recovery of nickel, cobalt and manganese in lithium-ion batteries to obtain a composite nickel material and mixing it with reduced graphene oxide prepared from graphite electrodes for use in supercapacitors, but the LiNi obtained by this method is 1 / 3 Co 1 / 3 Mn 1 / 3 The morphology of O2 materials is uncontrollable and has a significant negative impact on performance. Therefore, the recycling and reuse of lithium-ion batteries is very necessary. Summary of the invention

[0005] In view of the deficiencies of the prior art, an object of the present invention is to provide a method for preparing a supercapacitor material.

[0006] The purpose of the present invention is achieved through the following technical solutions.

[0007] A method for preparing a supercapacitor material comprises the following steps:

[0008] S1, mixing the first solution, the second solution, trimesic acid (BTC), polyvinyl pyrrolidone (PVP), N,N-dimethylformamide, anhydrous ethanol and water, stirring until transparent, and then performing a hydrothermal reaction to obtain a supercapacitor material precursor, wherein the first solution contains cobalt ions, and the second solution contains nickel ions, and the ratio of cobalt ions in the first solution to nickel ions in the second solution is (1-2): (1-2) by amount of substance, and the first solution satisfies situation 1 and / or the second solution satisfies situation 2, wherein situation 1 and situation 2 are as follows:

[0009] Case 1: All or part of the cobalt ions in the first solution come from the first leaching solution.

[0010] Case 2: All or part of the nickel ions in the second solution come from the second leaching solution;

[0011] The method for preparing the first leachate / the second leachate comprises steps 1 to 3:

[0012] Step 1, when used to prepare the first leachate, lithium cobalt oxide positive electrode waste is prepared as the positive electrode waste, and when used to prepare the second leachate, lithium nickel oxide positive electrode waste is prepared as the positive electrode waste;

[0013] In step 1, the lithium cobalt oxide positive electrode waste comes from the discharged waste lithium cobalt oxide batteries, and the lithium nickel oxide positive electrode waste comes from the discharged waste lithium nickel oxide batteries.

[0014] In step 1, the discharging method is to immerse the waste lithium cobalt oxide battery / waste lithium nickel oxide battery in a saturated NaCl aqueous solution for 24 to 48 hours.

[0015] Step 2, calcining the cathode waste at 450-600° C. for 0.5-1.5 h, soaking in a first solvent for 20-30 min after calcination, centrifuging, and drying to obtain a cathode material;

[0016] In step 2, the immersion is performed under ultrasonic conditions, and the frequency of the ultrasound is 30 to 40 kHz.

[0017] In step 2, the first solvent is water.

[0018] In step 2, the drying temperature is 50-70° C., and the drying time is 12-24 hours.

[0019] Step 3, mixing the positive electrode material and NH4Cl evenly, calcining at 300-400°C for 0.5-1h to obtain a mixture, and mixing the mixture with a second solvent to obtain a corresponding first leachate / second leachate.

[0020] In step 3, the second solvent is water.

[0021] In step 3, the ratio of the positive electrode material to NH4Cl is 1:(2-4) by mass.

[0022] In step 3, the ratio of the mass fraction of the mixture to the volume fraction of the second solvent is (2-3):(40-50), the unit of the mass fraction is g, and the unit of the volume fraction is mL.

[0023] In S1, the ratio of cobalt ions in the first leachate to nickel ions in the second leachate is (0-2):(0-2).

[0024] In S1, the stirring time is 25 to 35 minutes.

[0025] In S1, the ratio of the volume fraction of the first solution, the volume fraction of the second solution, the mass fraction of trimesic acid (BTC), the mass fraction of polyvinylpyrrolidone (PVP), the volume fraction of N,N-dimethylformamide, the volume fraction of anhydrous ethanol and the volume fraction of water is (1-10):(1-10):(0.21-0.42):(1-2):(5-15):(5-15):(1-10), the unit of the mass fraction is g, and the unit of the volume fraction is mL.

[0026] In S1, the concentration of cobalt ions in the first solution is 20-30 g / L, and the concentration of nickel ions in the second solution is 20-30 g / L.

[0027] In S1, the temperature of the hydrothermal reaction is 160-200° C., and the time of the hydrothermal reaction is 8-12 hours.

[0028] S2. In an argon or inert gas atmosphere, in a tubular furnace, placing the supercapacitor material precursor downstream of a gas flow of thiourea, heating the thiourea to sublime it, and heat-treating the supercapacitor material precursor at 300-400° C. for 1-3 hours to obtain a supercapacitor material, wherein the ratio of the supercapacitor material precursor to thiourea is 1:(4-6) by mass.

[0029] In S2, the heating rate to 300-400°C is 2-3°C / min.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] 1. The present invention utilizes cobalt and nickel in the positive electrode material of waste lithium batteries to synthesize the supercapacitor electrode material precursor (Ni x Co 3-x –MOF), and Ni x Co 3-x –MOF and thiourea are mixed to obtain supercapacitor electrode materials with good electrochemical properties (Ni x Co 3-x -S),Ni x Co 3-x -S retains Ni x Co 3-x -MOF has the characteristics of high porosity and large specific surface area. In the three-electrode test, the supercapacitor electrode material (Ni 1.5 Co 1.5 -S) has a specific capacitance of up to 595.0C / g (~1190.0F / g) at a current density of 1A / g, showing good electrochemical performance.

[0032] 2. The present invention synthesizes the supercapacitor electrode material precursor through a hydrothermal method. The technical solution has low cost and simple operation. It can not only replace the cobalt salts and nickel salts in chemicals to a certain extent to synthesize electrode materials, but also realize industrial practical operation to a certain extent, alleviating the economic pressure and water and soil pollution problems caused by cobalt and nickel in lithium batteries, and providing a new idea for industrial recovery of transition metals in waste lithium batteries and re-application of them in supercapacitor electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a SEM image of the supercapacitor material precursor prepared in Example 2;

[0034] Figure 2 This is a SEM image of the supercapacitor material prepared in Example 2;

[0035] Figure 3 This is a comparison curve of the volt-ampere characteristics of the supercapacitor materials prepared in Examples 1 to 5;

[0036] Figure 4 The constant current charge and discharge comparison curves of the supercapacitor materials prepared in Examples 1 to 5 at a current density of 1 A / g are shown;

[0037] Figure 5 The cyclic voltammetric characteristic curve of the supercapacitor material prepared in Example 2 at different scan rates;

[0038] Figure 6 This is a constant current charge and discharge curve diagram of the supercapacitor material prepared in Example 2 at different current densities;

[0039] Figure 7 This is a graph showing the capacitance contribution ratio of the supercapacitor material prepared in Example 2;

[0040] Figure 8 This is a constant current charge and discharge comparison curve of the supercapacitor material prepared in Comparative Example 1 and the supercapacitor material prepared in Example 2 at a current density of 1 A / g;

[0041] Fig. 9 The specific capacitance trend diagram of the supercapacitor materials prepared in Examples 1 to 5 at different current densities.

[0042] exist Figure 3 , Figure 4 and Fig. 9 In the example, “Ni0Co3-S” is the supercapacitor material prepared in Example 4, “Ni1Co2-S” is the supercapacitor material prepared in Example 1, and “Ni 1.5 Co 1.5 -S" is the supercapacitor material prepared in Example 2, "Ni2Co1-S" is the supercapacitor material prepared in Example 3, and "Ni3Co0-S" is the supercapacitor material prepared in Example 5. DETAILED DESCRIPTION

[0043] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0044] The raw materials and their manufacturers' information involved in the following examples are as follows:

[0045]

[0046] The instruments and their model information involved in the following embodiments are as follows:

[0047]

[0048] The water in the following examples is deionized water.

[0049] Examples 1 to 3

[0050] A method for preparing a supercapacitor material comprises the following steps:

[0051] S1, AmL of the first solution, BmL of the second solution and 10mL of N,N-dimethylformamide are mixed, the first solution is a first leachate containing cobalt ions, and the second solution is a second leachate containing nickel ions, and then 10mL of anhydrous ethanol and 10mL of water are added, and stirred evenly. In terms of the amount of substance, the ratio of cobalt ions in the first solution (first leachate) to nickel ions in the second solution (second leachate) is X; then 0.315g of trimesic acid (BTC) and 2g of polyvinyl pyrrolidone (PVP) are added, and stirred for 30min until transparent, and hydrothermally reacted in a reactor (volume of 100ml) at 180°C for 10h to obtain a supercapacitor material precursor (Ni x Co 3-x –MOF);

[0052] S2, in an argon atmosphere, disperse the supercapacitor material precursor in a porcelain boat, put the porcelain boat into a tube furnace, and then put thiourea into the tube furnace so that the thiourea is close to the air inlet of the tube furnace and the supercapacitor material precursor is far away from the air inlet (the supercapacitor material precursor is placed downstream of the thiourea gas flow), and heat treat at 350 ° C for 2h to obtain a supercapacitor material (Ni x Co 3-x -S) (because the heating wires are distributed throughout the furnace, the heating temperature of thiourea is the same as that of the supercapacitor material precursor). In terms of mass fraction, the ratio of the supercapacitor material precursor to thiourea is 1:5, and the heating rate to 350°C is 2°C / min.

[0053] The method for preparing the first leachate and the second leachate comprises steps 1 to 3:

[0054] Step 1, soaking the waste lithium cobalt oxide battery and the waste lithium nickel oxide battery in a saturated NaCl aqueous solution at 25° C. for 24 hours respectively until they are fully discharged, removing the shells of the waste lithium cobalt oxide battery and the waste lithium nickel oxide battery, separating the positive and negative electrodes and the separator, and obtaining lithium cobalt oxide positive electrode waste and lithium nickel oxide positive electrode waste;

[0055] Step 2, calcining the lithium cobalt oxide positive electrode waste and the lithium nickel oxide positive electrode waste in a muffle furnace at 500° C. for 1 hour, respectively, and after calcination, immersing them in a first solvent (water) for ultrasonic treatment for 30 minutes at an ultrasonic frequency of 40 kHz, centrifuging, and drying at 60° C. for 12 hours to obtain a lithium cobalt oxide positive electrode material and a lithium nickel oxide positive electrode material, respectively;

[0056] Step 3, mixing the lithium cobalt oxide positive electrode material and NH4Cl, grinding them in a mortar until they are uniform, calcining them in a muffle furnace at 350° C. for 1 hour to obtain a mixture, mixing the mixture with a second solvent (water), filtering out impurities, obtaining a first leachate, and subjecting the first leachate to an ICP-OES test. The ICP-OES test shows that the cobalt ion concentration in the first leachate is 26.4 g / L;

[0057] The lithium nickelate positive electrode material and NH4Cl were mixed, ground in a mortar until uniform, and calcined in a muffle furnace at 350°C for 1 hour to obtain a mixture. The mixture was mixed with a second solvent (water), and impurities were filtered out to obtain a second leachate. The second leachate was subjected to ICP-OES test, and the ICP-OES test showed that the nickel ion concentration in the second leachate was 24.5 g / L.

[0058] Among them, in terms of mass fractions, the ratio of the lithium cobalt oxide positive electrode material to NH4Cl in the process of preparing the first leaching solution is 1:4, the ratio of the lithium nickel oxide positive electrode material to NH4Cl in the process of preparing the second leaching solution is 1:4, the ratio of the mass fraction of the mixture in the process of preparing the first leaching solution to the volume fraction of the second solvent (water) is 2:40, and the ratio of the mass fraction of the mixture in the process of preparing the second leaching solution to the volume fraction of the second solvent (water) is 2:40. The unit of mass fraction is g, and the unit of volume fraction is mL.

[0059] The X value, A value and B value are shown in Table 1.

[0060] Table 1

[0061] Example X (molar ratio) A(unit: mL) B (unit: mL) Example 1 2:1 4.47 2.4 Example 2 1.5:1.5 3.35 3.6 Example 3 1:2 2.23 4.8

[0062] Example 4

[0063] A method for preparing a supercapacitor material comprises the following steps:

[0064] S1, 6.6 mL of the first leachate in Example 1 and 10 mL of N, N-dimethylformamide were mixed, and then 10 mL of anhydrous ethanol and 10 mL of water were added, and the mixture was stirred evenly, and then 0.315 g of trimesic acid (BTC) and 2 g of polyvinyl pyrrolidone (PVP) were added, and the mixture was stirred for 30 min until transparent, and heated in a reactor (volume of 100 ml) at 180° C. for 10 h to obtain a supercapacitor material precursor;

[0065] S2, under argon atmosphere, disperse the supercapacitor material precursor in a porcelain boat, put the porcelain boat into a tubular furnace, and then put thiourea into the tubular furnace so that the thiourea is close to the air inlet of the tubular furnace and the supercapacitor material precursor is away from the air inlet (the supercapacitor material precursor is placed downstream of the air flow of the thiourea), and heat treat at 350°C for 2h to obtain the supercapacitor material (Ni0Co3-S) (because the heating wire is distributed throughout the furnace, the heating temperature of the thiourea is the same as that of the supercapacitor material precursor). In terms of mass fraction, the ratio of the supercapacitor material precursor to thiourea is 1:5, and the heating rate to 350°C is 2°C / min.

[0066] Example 5

[0067] A method for preparing a supercapacitor material comprises the following steps:

[0068] S1, 7.2 mL of the second leachate in Example 1 and 10 mL of N, N-dimethylformamide were mixed, and then 10 mL of anhydrous ethanol and 10 mL of water were added, and the mixture was stirred evenly, and then 0.315 g of trimesic acid (BTC) and 2 g of polyvinyl pyrrolidone (PVP) were added, and the mixture was stirred for 30 min until transparent, and heated in a reactor (volume of 100 ml) at 180° C. for 10 h to obtain a supercapacitor material precursor;

[0069] S2, under argon atmosphere, disperse the supercapacitor material precursor in a porcelain boat, put the porcelain boat into a tubular furnace, and then put thiourea into the tubular furnace so that the thiourea is close to the air inlet of the tubular furnace and the supercapacitor material precursor is away from the air inlet (the supercapacitor material precursor is placed downstream of the air flow of the thiourea), and heat treat at 350°C for 2h to obtain the supercapacitor material (Ni3Co0-S) (because the heating wire is distributed throughout the furnace, the heating temperature of the thiourea is the same as that of the supercapacitor material precursor). In terms of mass fraction, the ratio of the supercapacitor material precursor to thiourea is 1:5, and the heating rate to 350°C is 2°C / min.

[0070] Comparative Example 1

[0071] A method for preparing a supercapacitor material comprises the following steps:

[0072] S1, 1.5mmol CoCl2·6H2O, 1.5mmol NiCl2·6H2O and 10ml N,N-dimethylformamide (DMF) were mixed, 10ml anhydrous ethanol and 10ml deionized water were added, and stirred evenly, and then 0.315g trimesic acid and 2g PVP were added, and stirred until a transparent solution was obtained, and poured into a 100ml reactor and reacted at 180℃ for 10h to obtain Ni 1.5 Co 1.5 -MOF;

[0073] S2, in an argon atmosphere, Ni 1.5 Co 1.5 -MOF is dispersed in a porcelain boat, and the porcelain boat and thiourea are placed in a tube furnace, with thiourea close to the air inlet of the tube furnace. 1.5 Co 1.5 -MOF is far from the air inlet (Ni 1.5 Co 1.5 -MOF was placed in the downstream of the thiourea gas flow) and heat treated at 350 ° C for 2 h to obtain a supercapacitor material (Ni 1.5 Co 1.5 -MOF-D) (Because the heating wires are distributed throughout the furnace, the heating temperature of thiourea is similar to that of Ni 1.5Co 1.5 -MOF), by weight, Ni 1.5 Co 1.5 The ratio of -MOF to thiourea was 1:5, and the heating rate to 350 °C was 2 °C / min.

[0074] The supercapacitor materials prepared in Examples 1 to 5 and Comparative Example 1 were respectively subjected to electrochemical performance tests using three electrodes: the reference electrode was Hg / HgO, the counter electrode was a 1×1 cm platinum sheet, and the electrolyte was a 6 mol / L KOH aqueous solution, wherein the working electrode was prepared by mixing the supercapacitor material, acetylene black, polytetrafluoroethylene (PTFE) and anhydrous ethanol in a ratio of 8:1:1:1 to supercapacitor material, acetylene black, polytetrafluoroethylene (PTFE) and anhydrous ethanol in parts by mass, drying, repeatedly rolling, cutting 1×1 cm and pressing it on a 1.5×2 cm nickel foam using a tablet press to obtain a working electrode.

[0075] Depend on Figure 1 and Figure 2 It can be seen that the supercapacitor material precursor obtained by the present invention is spherical, and the supercapacitor material obtained by sulfurization retains the original form of the supercapacitor material precursor. Different from the smooth spherical surface of the supercapacitor material precursor, the surface of the supercapacitor material is covered with a porous network structure of nanoparticles. It can be foreseen that the changes in specific surface area and active sites brought about by the evolution of morphology and structure will affect its final electrochemical performance. Among them, the specific surface area of ​​the supercapacitor material precursor of Example 2 is 5.1m 2 / g, the supercapacitor material obtained after sulfurization (Ni 1.5 Co 1.5 -S) specific surface area can reach 35.1m 2 / g.

[0076] Figure 3 The volt-ampere characteristic comparison curve of the supercapacitor materials prepared in Examples 1 to 5 is shown in FIG. Figure 3 It can be seen that the supercapacitor materials prepared in Examples 1 to 5 all have obvious redox peaks and are battery-type electrode materials. 1.5 Co 1.5 -S has the largest redox peak area, indicating that Ni 1.5 Co 1.5 -S has the largest specific capacitance.

[0077] To further confirm that Ni 1.5 Co 1.5 -S has the largest specific capacitance, and a three-electrode constant current charge and discharge test is performed, such as Figure 4 As shown, Ni is obtained by calculation 1.5Co 1.5 -S has a specific capacitance of 595C / g (~1190F / g), Ni0Co3-S has a specific capacitance of 85.3C / g (~170.6F / g), Ni1Co2-S has a specific capacitance of 481.8C / g (~963.6F / g), Ni2Co1-S has a specific capacitance of 457.6C / g (~915.2F / g), and Ni3Co0-S has a specific capacitance of 322.7C / g (~645.4F / g).

[0078] like Figure 5 As shown in Figure 2, with the increase of scanning rate, Ni 1.5 Co 1.5 -S (the supercapacitor material prepared in Example 2) has a redox peak that gradually increases, and as the scan rate increases, the electrode is polarized to varying degrees, and the position of the redox peak shifts.

[0079] Fig. 9 The specific capacitance trend diagram of the supercapacitor materials prepared in Examples 1 to 5 at different current densities. Figure 6 The supercapacitor material (Ni 1.5 Co 1.5 -S) constant current charge and discharge curves at different current densities. By calculation, it can be seen that when the current density is 1A / g, Ni 1.5 Co 1.5 -S has the maximum specific capacitance. When the current density is 2A / g, Ni 1.5 Co 1.5 -S has a specific capacitance of 575.6C / g (~1151.2F / g). When the current density is 3A / g, Ni 1.5 Co 1.5 -S has a specific capacitance of 545.6C / g (~1091.2F / g). When the current density is 5A / g, Ni 1.5 Co 1.5 -S has a specific capacitance of 490.5C / g (~981.0F / g). When the current density is 10A / g, Ni 1.5 Co 1.5 -S has a specific capacitance of 440.0 C / g (~880.0 F / g).

[0080] Using the power law (i p =av b ) to evaluate the peak response (i p ) and scan rate (v), where b = 0.5 represents a diffusion-controlled current response, and b = 1.0 represents a capacitance-controlled process. Figure 7It can be seen that the calculated values ​​of the supercapacitor material prepared in Example 2 are 0.57 and 0.61, respectively, indicating that the electrode energy storage is mainly diffusion-controlled behavior.

[0081] like Figure 8 As shown, the supercapacitor material prepared in Example 2 ( Figure 8 Chinese Ni 1.5 Co 1.5 -MOF) and the supercapacitor material prepared in Comparative Example 1 ( Figure 8 Chinese Ni 1.5 Co 1.5 -MOF-D) was used for constant current charge and discharge performance comparison. The specific capacitance of the supercapacitor material prepared in Example 2 was 595C / g (~1190F / g), and the specific capacitance of the supercapacitor material prepared in Comparative Example 1 was 627.5C / g (~1255.0F / g). Under the same conditions that the molar ratio of cobalt ions and nickel ions was 1.5:1.5, the specific capacitance of the supercapacitor material prepared by recycling cobalt and nickel from waste lithium batteries was basically the same as that of the supercapacitor material prepared by cobalt salts and nickel salts, indicating that it is feasible to recycle cobalt and nickel from waste lithium batteries to prepare supercapacitor materials in the present invention.

[0082] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a supercapacitor material, characterized in that: The following steps are involved: S1, mixing the first solution, the second solution, trimesic acid, polyvinyl pyrrolidone, N,N-dimethylformamide, anhydrous ethanol and water, stirring until transparent, and then performing a hydrothermal reaction to obtain a supercapacitor material precursor, wherein the first solution contains cobalt ions, and the second solution contains nickel ions, and the ratio of cobalt ions in the first solution to nickel ions in the second solution is (1-2): (1-2) in terms of the amount of substance, and the first solution satisfies situation 1 and / or the second solution satisfies situation 2, wherein situation 1 and situation 2 are as follows: Case 1: All or part of the cobalt ions in the first solution come from the first leaching solution. Case 2: All or part of the nickel ions in the second solution come from the second leaching solution; S2, in an argon or inert gas atmosphere, in a tube furnace, placing the supercapacitor material precursor downstream of a gas flow of thiourea, heating the thiourea to sublime it, and heat-treating the supercapacitor material precursor at 300-400° C. for 1-3 hours to obtain a supercapacitor material, wherein the ratio of the supercapacitor material precursor to thiourea is 1:(4-6) by mass; The method for preparing the first leachate / the second leachate comprises steps 1 to 3: Step 1, when used to prepare the first leachate, lithium cobalt oxide positive electrode waste is prepared as the positive electrode waste, and when used to prepare the second leachate, lithium nickel oxide positive electrode waste is prepared as the positive electrode waste; Step 2, calcining the cathode waste at 450-600° C. for 0.5-1.5 h, soaking in a first solvent for 20-30 min after calcination, centrifuging, and drying to obtain a cathode material; Step 3, mixing the positive electrode material and NH4Cl evenly, calcining at 300-400°C for 0.5-1h to obtain a mixture, and mixing the mixture with a second solvent to obtain a corresponding first leachate / second leachate.

2. The preparation method according to claim 1, characterized in that: In step 1, the lithium cobalt oxide positive electrode waste comes from the discharged waste lithium cobalt oxide batteries, and the lithium nickel oxide positive electrode waste comes from the discharged waste lithium nickel oxide batteries.

3. The preparation method according to claim 1, characterized in that: In S1, the ratio of cobalt ions in the first leachate to nickel ions in the second leachate is (0-2):(0-2). In S1, the concentration of cobalt ions in the first solution is 20-30 g / L, and the concentration of nickel ions in the second solution is 20-30 g / L.

4. The preparation method according to claim 1, characterized in that: In step 3, the ratio of the positive electrode material to NH4Cl is 1:(2-4) by mass.

5. The preparation method according to claim 1, characterized in that: In step 3, the ratio of the mass fraction of the mixture to the volume fraction of the second solvent is (2-3):(40-50), the unit of the mass fraction is g, and the unit of the volume fraction is mL.

6. The preparation method according to claim 1, characterized in that: In S1, the ratio of the volume fraction of the first solution, the volume fraction of the second solution, the mass fraction of trimesic acid, the mass fraction of polyvinylpyrrolidone, the volume fraction of N,N-dimethylformamide, the volume fraction of anhydrous ethanol and the volume fraction of water is (1-10):(1-10):(0.21-0.42):(1-2):(5-15):(5-15):(1-10), the unit of the mass fraction is g, and the unit of the volume fraction is mL.

7. The preparation method according to claim 1, characterized in that: In S1, the temperature of the hydrothermal reaction is 160-200° C., and the time of the hydrothermal reaction is 8-12 hours.

8. The preparation method according to claim 1, characterized in that: In step 1, the discharging method is to immerse the waste lithium cobalt oxide battery / waste lithium nickel oxide battery in a saturated NaCl aqueous solution for 24 to 48 hours.

9. The preparation method according to claim 1, characterized in that: In step 2, the first solvent is water, in step 3, the second solvent is water, in step 2, the immersion is carried out under ultrasonic conditions, the frequency of the ultrasound is 30 to 40 kHz, in step 2, the drying temperature is 50 to 70°C, and the drying time is 12 to 24 hours.

10. The preparation method according to claim 1, characterized in that: In S1, the stirring time is 25 to 35 minutes, and in S2, the heating rate to 300 to 400°C is 2 to 3°C / min.

Citation Information

Patent Citations

  • Method of preparing CoPi catalyst through green recovered waste lithium cobaltate battery

    CN110756191A

  • Method for efficiently recycling positive and negative electrode materials of lithium ion battery as supercapacitor electrode materials

    CN111048862A